2006
DOI: 10.1093/ps/85.3.563
|View full text |Cite
|
Sign up to set email alerts
|

Use of a litter material made from cotton waste, gypsum, and old newsprint for rearing broiler chickens

Abstract: Three experiments, which included 4 broiler flocks, were conducted to examine the usefulness of a novel bedding material for rearing broilers. The control bedding was pine shavings. The novel bedding, aGroChips (AC), was a chopped material made from cotton lint waste, gypsum, and old newsprint using a proprietary paper manufacturing process (Novovita, Inc., Raleigh, NC). All birds were fed the same feeding program: starter from 0 to 3 wk, grower from 3 to 5 or 6 wk, and finisher during the last week. Birds wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 10 publications
9
28
0
Order By: Relevance
“…These results are similar to those described by Mizubuti et al (1994), who evaluated rice husks, guinea grass, and napier grass as litter material. On the other hand, opposite results were obtained by Mendes et al (1987), Santos et al (2000), Chamblee & Yeatman (2003), Grimes et al (2006), Atapattu & Wickramasinghe (2007), Araújo et al (2007), and Ávila et al (2008), who tested different broiler litter materials and did not find any differences in body weight or feed intake. Moreover, Toghyani et al (2009) studied five broiler litter materials and observed significant reduction of body weight, feed intake, and antibody titers in broilers reared on rice husks litter.…”
Section: Resultsmentioning
confidence: 82%
“…These results are similar to those described by Mizubuti et al (1994), who evaluated rice husks, guinea grass, and napier grass as litter material. On the other hand, opposite results were obtained by Mendes et al (1987), Santos et al (2000), Chamblee & Yeatman (2003), Grimes et al (2006), Atapattu & Wickramasinghe (2007), Araújo et al (2007), and Ávila et al (2008), who tested different broiler litter materials and did not find any differences in body weight or feed intake. Moreover, Toghyani et al (2009) studied five broiler litter materials and observed significant reduction of body weight, feed intake, and antibody titers in broilers reared on rice husks litter.…”
Section: Resultsmentioning
confidence: 82%
“…In other countries, FPD is classified into 3 to 11 categories [11,15,[17][18][19]27]. FPD is examined macroscopically, and the area/size of each footpad is unequal, depending on age.…”
Section: Examination At Slaughterhousesmentioning
confidence: 99%
“…In poultry production, attempts have been made to use and test several types of material for litter: refined gypsum (Wyatt & Goodman, 1992;Grimes et al, 2006), recycled paper chips from waste newspapers (Lien et al, 1992), pelletized newspaper (Frame et al, 2002;Grimes et al, 2006), tree core-like kenaf core (Malone et al, 1990;Brake et al, 1993), particleboard residues (Hester et al, 1997), leaves (Willis et al, 1997), sand (Bilgili et al, 1999;Arnould et al, 2004), cotton waste (Grimes et al, 2006), hazelnut husks or wheat stalks (Sarica & Cam, 2000), wood shavings (Shields et al, 2005;Macklin et al, 2005), rice hulls (Swain & Sundaram, 2000;Shields et al, 2004), rice hull ashes (Chamblee et al, 2003), coffee husk (Ortiz et al, 2003;Ortiz et al, 2006), saw dust (Mendes et al, 2011), coir dust (Swain & Sundaram, 2000), straw (Al Homidan & Robertson,2003), feathers (Sanotra et al, 1995;Gunnarson et al, 2000), sugarcane bagasse or peat (Petherick & Duncan, 1989). The use of any of these substrates most often depends on the availability in each area and at each moment.…”
Section: Introductionmentioning
confidence: 99%